The SAGE handbook of European studies - Rumford, Chris (Los Angeles [Calif.] ;London : SAGE, 2009)
This handbook promotes the increasing diversity of perspectives employed in the study of contemporary Europe and EU integration, and is situated in the context of Europe's transformations. It offers balanced coverage of political, social, economic, cultur
Introduction: The Stuff of European Studies / Chris Rumford -- Europe Transformed, 1945-2000 / Charles Tilly -- The European Heritage: History, Memory, and Time / Gerard Delanty -- Europe Beyond East and West.
Includes bibliographical references and index.
Keywords: Avrupa -- Politika ve hükümet -- 1989-.; Europe -- Politics and government -- 1989-.; Avrupa -- Ekonomik koşullar -- 21. Yüzyıl; Europe -- Economic conditions -- 21st century; Avrupa -- Sosyal koşullar -- 21. Yüzyıl; Europe -- Social conditions -- 21st century; Avrupa -- Uygarlık -- 21. Yüzyıl; Europe -- Civilization -- 21st century